Climate change enhanced the positive contribution of human activities to net ecosystem productivity from 1983 to 2018 - Liu, Min; Bai, Xiaoyong; Tan, Qiu; Luo, Guangjie; Zhao, Cuiwei; Wu, Luhua; Chen, Fei; Li, Chaojun; Yang, Yujie; Ran, Chen; Luo, Xuling; Zhang, Sirui (Frontiers in Ecology and Evolution, 2023)
Accurate assessment of the net ecosystem productivity (NEP) is very important for understanding the global carbon balance. However, it remains unknown whether climate change (CC) promoted or weakened the impact of human activities (HA) on the NEP from 1983 to 2018. Here, we quantified the contribution of CC and HA to the global NEP based on a boosted regression tree model and sensitivity analysis. The results show that (1) a total of 69% of the areas showed an upward trend in the NEP, with HA and CC controlled 36.33% and 32.79% of the NEP growth, respectively. While, the contribution of HA (HA_con) far exceeded that of CC by 6.4 times. (2) The CO2 concentration had the largest positive contribution (37%) to NEP and the largest influence area (32.5%). It made the most significant contribution to the NEP trend in the range of 435–440 ppm. In more than 50% of the areas, the main loss factor was solar radiation (SR) in any control area of the climate factors. (3) Interestingly, CC enhanced the positive HA_con to the NEP in 44% of the world, and in 25% of the area, the effect was greater than 50%. Our results shed light on the optimal range of each climatic factor for enhancing the NEP and emphasize the important role of CC in enhancing the positive HA_con to the NEP than found in previous studies.